BENTUK PENATAAN KAWASAN DAN PERMUKIMAN KAMPUNG AUR MEDAN - Dasrizal, Dasrizal; Irwansyah, Irwansyah (Universitas Quality, 2019)
The Settlement Area in Kampung Aur is a densely populated settlement located on the banks of the Deli River in Medan. Until now there has not been a more appropriate solution to the arrangement of the area and its residents although there are in several cities there have been several types of solutions to the problem of densely populated settlements ranging from forced evictions, the construction of new settlements in the form of flat / flat and village improvement programs. That said, the government began to realize that the problem could not be solved by a one-way system. There must be communication with slum dwellers. This then encourages the authors to make an arrangement of the area and its residents with an approach to the behavior of citizens and the types of settlements at this time. This study aims to produce a design of the area and settlements that can accommodate social and cultural aspects of society through the approach of environmental behavior and types of settlements. To achieve this goal, participatory observation will be carried out in every dominant community in the location. Through this observation it will be seen how the environmental settings and behavior work in Kampung Aur. Data on environmental and behavioral settings will then be processed to produce Kampung Aur design completion criteria. From this study it was found that there are two dominant tribes in Kampung Aur, namely Chinese and Minang.